Macromolecular structure determination using X‐rays, neutrons and electrons: recent developments in Phenix. Issue 10 (7th October 2019) - Liebschner, Dorothee; Afonine, Pavel V.; Baker, Matthew L.; Bunkóczi, Gábor; Chen, Vincent B.; Croll, Tristan I.; Hintze, Bradley; Hung, Li-Wei; Jain, Swati; McCoy, Airlie J.; Moriarty, Nigel W.; Oeffner, Robert D.; et al.
Abstract : Recent developments in the Phenix software package are described in the context of macromolecular structure determination using X‐rays, neutrons and electrons. Abstract : Diffraction (X‐ray, neutron and electron) and electron cryo‐microscopy are powerful methods to determine three‐dimensional macromolecular structures, which are required to understand biological processes and to develop new therapeutics against diseases. The overall structure‐solution workflow is similar for these techniques, but nuances exist because the properties of the reduced experimental data are different. Software tools for structure determination should therefore be tailored for each method. Phenix is a comprehensive software package for macromolecular structure determination that handles data from any of these techniques. Tasks performed with Phenix include data‐quality assessment, map improvement, model building, the validation/rebuilding/refinement cycle and deposition. Each tool caters to the type of experimental data. The design of Phenix emphasizes the automation of procedures, where possible, to minimize repetitive and time‐consuming manual tasks, while default parameters are chosen to encourage best practice. A graphical user interface provides access to many command‐line features of Phenix and streamlines the transition between programs, project tracking and re‐running of previous tasks.